1966
DOI: 10.1113/jphysiol.1966.sp008033
|View full text |Cite
|
Sign up to set email alerts
|

Contractures in a superfused frog's ventricle

Abstract: 1. A new perfused preparation of frog's ventricle is described, whose main advantage is that there are short diffusion distances between the cells and the washing fluid. 2. This preparation responds within a few seconds to alterations in sodium, potassium or calcium concentration, or alteration in the osmotic pressure of the bathing fluid. The speed of these alterations is consistent with the diffusional distances involved measured histologically. 3. On depolarizing the preparation with Ringer + excess potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…This twitch prolongs the time to peak con-tracture tension by a variable but small amount. As the peak tension declines relatively slowly with a T, of 40-60 sec (Lamb & McGuigan, 1966) this should not greatly affect the tension developed, and comparison of equivalent points on contracture records before and after adrenaline confirmed that in fact this had less than a 5 % effect on peak twitch tension. It might be supposed however that the presence of this spike could be reducing the contracture tension in some other way, and experiments were carried out in situations where this initial twitch could be abolished.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This twitch prolongs the time to peak con-tracture tension by a variable but small amount. As the peak tension declines relatively slowly with a T, of 40-60 sec (Lamb & McGuigan, 1966) this should not greatly affect the tension developed, and comparison of equivalent points on contracture records before and after adrenaline confirmed that in fact this had less than a 5 % effect on peak twitch tension. It might be supposed however that the presence of this spike could be reducing the contracture tension in some other way, and experiments were carried out in situations where this initial twitch could be abolished.…”
Section: Introductionmentioning
confidence: 80%
“…Half ventricles were pinned out cutsideuppermost by two entomological pins and irrigated with a jet of Ringer solution (Lamb & McGuigan, 1966). The third 'corner' of the ventricle was connected by a short length of Arbrasilk 4/0 thread to a Grass FTO 3 transducer used on its most sensitive range.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, using a variation of the [K]o to alter the membrane potential, no N-shaped tension-depolarization curves have been found. It is interesting to note that other reports using the potassium contracture method also provide simple sigmoidal curves (Lamb & McGuigan, 1966;Gibbons & Fozzard, 1971 (Fig. 5), tension increasing parabolically between 3 and 25 mM-K (-75 to -40 mV resting potential) followed by a more linear increase as the membrane potential is lowered from -40 to -15 mV (25-100 mM-K).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, the rate of Ca extrusion by the Ca-Na exchange mechanism will be unchanged if both [Ca] Contraction in a Na-free medium. After removal of external Na, development of reversible contractures without any marked depolarization has been observed in frog ventricular and atrial preparations (Luttgau & Niedergerke, 1958;Lamb & McGuigan, 1966;Vassort, 1973;Chapman, 1974), guinea-pig auricles and atrial trabeculae of calf hearts (Scholz, 1969a, b) and ventricular strips of the goldfish heart (Busselen & Carmeliet, 1973). The simplest interpretation of a Na-lack contracture is that transmembrane exchange of internal Ca for external Na is inhibited in a Na-free medium and the control of the internal Ca level is left to some other mechanism which, under normal conditions, is inferior to the pumping mechanism of the sarcolemma.…”
mentioning
confidence: 99%
“…The system is thought to operate close to equilibrium at any potential, thereby determining the INTRODUCTION It has long been known that force development in cardiac muscle is promoted by Ca ions and depressed by Na ions in the bathing medium (Ringer, 1883;Clark, 1913;Daly & Clark, 1921). The antagonistic effects have been quantified by the observation that the contractile strength of the frog heart, both ventricle and auricle, depends largely on the ratio of [Ca]o/[Na]2 (Wilbrandt & Koller, 1948;Luttgau & Niedergerke, 1958;Lamb & McGuigan, 1966;Chapman & Tunstall, 197t). This relation holds for twitch tension initiated by an action potential as well as contractures induced by high-K solutions.…”
mentioning
confidence: 99%